Effect of cobalt content on the electrochemical properties and structural stability of NCA type cathode materials. Issue 35 (28th August 2018) - Ghatak, Kamalika; Basu, Swastik; Das, Tridip; Sharma, Vidushi; Kumar, Hemant; Datta, Dibakar
Abstract : Computational design of environmentally benign low-cost, cathode materials with reduced cobalt concentration. Abstract : At present, the most common type of cathode materials, NCA (Li1− x Ni0.80 Co0.15 Al0.05 O2, x = 0 to 1), have a very high concentration of cobalt. Since cobalt is toxic and expensive, the existing design of cathode materials is neither cost-effective nor environmentally benign. We have performed density functional theory (DFT) calculations to investigate electrochemical, electronic, and structural properties of four types of NCA cathode materials with the simultaneous decrease in Co content along with the increase in Ni content. Our results show that even if the cobalt concentration is significantly decreased from 16.70% (NCA_I) to 4.20% (NCA_IV), variation in intercalation potential and specific capacity is not significant. For example, in the case of 50% Li concentration, the voltage drop is only ∼17% while the change in specific capacity is negligible. Moreover, we have also explored the influence of sodium doping in the intercalation site on the electrochemical, electronic, and structural properties. By considering two extreme cases of NCAs ( i.e., with highest and lowest Co content: NCA_I and NCA_IV, respectively), we have demonstrated the importance of Na doping from the structural and electronic point of view. Our results provide insight into the design of environmentally benign, low-cost cathode materials with reduced cobalt concentration.